Bacterial endophytes: a reservoir of bioactive anti-microbial compounds - Cheah, Yoke Kqueen; Mohamed Rafi, Mohamed Ikhtifar (Scienceline Publications, 2018)
Bacterial endophytes are found on all types of plants and is a potential source of bioactive compounds which can be utilized to fight against multi-resistant pathogens and could be further develop into new leads for antibiotic development. However, the research done on the bacterial endophytes is relatively new and has potential to grow as it is theorized that each plant has one or more bacterial endophytes inhabiting them. This review aims to review the studies that have been done previously and give new insights on the latest trends in this field of research.